Investor sentiment and the market reaction to dividend news: European evidence - Vieira, Elisabete F. Simões (2012)
Purpose: This paper examines the effect of investor sentiment on the market reaction to dividend change announcements. Design/methodology/approach: We use the European Economic Sentiment Indicator data, from Directorate General for Economic and Financial Affairs (DG ECFIN), as a proxy for investor sentiment and focus on the market reaction to dividend change announcements, using panel data methodology. Findings: Using data from three European markets, our results indicate that the investor sentiment has some influence on the market reaction to dividend change announcements, for two of the three analysed markets. Globally, we find no evidence of investor sentiment influencing the market reaction to dividend change announcements for the Portuguese market. However, we find evidence that the positive share price reaction to dividend increases enlarges with sentiment, in the case of the UK markets, whereas the negative share price reaction to dividend decreases reduces with sentiment, in the French market. Research limitations/implications: We have no access to dividend forecasts, so, our findings are based on naïve dividend changes and not unexpected change dividends. Originality/value: This paper offers some insights on the effect of investor sentiment on the market reaction to firms’ news, a strand of finance that is scarcely developed and contributes to the analysis of European markets that are in need of research. As the best of our knowledge, this is the first study to analyse the effect of investor sentiment on the market reaction to dividend news, in the context of European markets.